The human fertilisation and embryology authority - Leather, Suzi (Henry Stewart Talks, 2007)
Background to UK regulation of embryo research and hESC research, The Human Fertilisation & Embryology Act (1990), The licensing process, Strengthening science through regulation, Public attitudes towards embryo research and regulation, Challenges to public consensus, Future of embryo research